Nitrogen, phosphorus and sulfur utilization by fungi (Cambridge Univ, 1989)
Nitrogen, phosphorus and sulfur are the major mineral nutrient elements in the biosphere and fungi play an essential role in their release from organic residues in terrestrial ecosystems, thus influencing plant nutrition and primary productivity. This book covers four basic areas: the physiology and metabolism of nitrogen, phosphorus and sulfur in fungi; the role of these minerals in pathogenic relationships with plants; their role in mutualistic relationships with plants (especially mycorrhizas, but lichens too);and the role of fungi in cycling of these elements within ecosystems